1998
DOI: 10.1097/00006842-199809000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Groups and Depressed Mood as Predictors of 22-Month Mortality in Medical Inpatients

Abstract: Depressed mood is an independent risk factor for all-cause mortality in medical inpatients. Identifying patients at risk does not require formal psychiatric diagnoses, but can be achieved by means of a short, routinely administered self-rating questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 33 publications
6
67
0
2
Order By: Relevance
“…High depression and anxiety values have both been shown to predict subsequent mortality [3,7]. However, in some cases, symptoms of depression but not anxiety in multivariate models predicted mortality [5,6], and in some, neither depression nor anxiety symptoms were found to predict mortality in MI patients [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High depression and anxiety values have both been shown to predict subsequent mortality [3,7]. However, in some cases, symptoms of depression but not anxiety in multivariate models predicted mortality [5,6], and in some, neither depression nor anxiety symptoms were found to predict mortality in MI patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the question arises whether depression following MI is a risk factor for cardiovascular morbidity and mortality. Although the number of positive studies in this field has been growing steadily, the discrepancies have continued since the publication of a few negative results [3][4][5][6][7][8][9]. Scant studies have Seyed Hamzeh Hosseini et al, Anxiety and depression as predictors of MI mortality reported longer-term mortality data in MI patients; whereas one has found an association between an in-hospital depression and mortality 5 years later [10], the other has observed no association at 3-year follow-up [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, depressive symptoms that are not sufficient in magnitude to meet the criteria for major depression occur at least as commonly among cardiac patients. 2,3 Recent epidemiological studies evaluating the relationship between depression and CAD among healthy [3][4][5][6][7][8][9][10][11] and CAD [12][13][14][15][16][17][18][19] populations consistently demonstrate a significant prospective relationship between the occurrence of major depression episodes and the incidence of cardiac events (Table 1). Two additional findings are notable.…”
Section: Depression and Related Syndromesmentioning
confidence: 99%
“…The epidemiological investigation of anxiety disorders among CAD patients has also been quite sparse. Because 4 small studies have each noted a relationship between anxiety and a constellation of hard and soft cardiac events among CAD patients (Table 2), 17,18,47,48 more large-scale epidemiological studies among CAD patients now appear to be warranted.…”
Section: Anxiety Syndromesmentioning
confidence: 99%
“…Also, an association between depressed mood and sleep disturbance has been reported based on a cohort of 3880 patients in Germany [3]. Moreover, depressed mood has been proposed as an independent risk factor for 22-month mortality in physically ill patients [4].…”
Section: Introductionmentioning
confidence: 96%